Eco‐engineering in urbanised coastal systems: consideration of social values. (5th January 2016) - Morris, Rebecca L.; Deavin, Gemma; Hemelryk Donald, Stephanie; Coleman, Ross A.
Summary: Loss of marine habitats due to urbanisation has been met with growing research efforts to mitigate ecological impacts through eco‐engineering. Research in this area has focused on scientific and engineering outcomes, not considering that seawalls are a socially driven insertion into the environment. Further, management concerns when employing eco‐engineering projects include public opinion regarding the aesthetic value of enhanced structures. It is therefore important for ecologists working in urban systems to understand how the public connects with the environment. Here, we used surveys to quantify perceptions of marine environmental issues and attitudes towards an example of eco‐engineering research from Sydney Harbour, Australia. We also evaluated the effect of disclosing the costs of enhancing seawalls to participants regarding their support for the initiative. Results showed there was high support for applied management to improve biodiversity. This result is promising for the implementation of future eco‐engineering projects. Understanding social values towards our coastlines and new conservation initiatives will provide end users with the tools to optimise coastal management plans. In summary, consideration of public values in urban conservation is essential for effective management.